ANALISIS TERHADAP DASAR PERTIMBANGAN HAKIM DALAM PENERAPAN ALASAN PEMAAF DAN ALASAN YANG MERINGANKAN HUKUMAN PADA PELAKU TINDAK PIDANA PENCURIAN DIMASA PANDEMI COVID-19 DI RIAU - Purba, Rantika Br.; Deliana, Evi; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
As a rule of law based on the values of Pancasila and the 1945 constitution of the Republic of Indonesia, the birth of an independent and partial judiciary si one of the main pillars. Realizing the rule of law in national and state life Law Number 48 of 2009 concerning judicial power states that judges must explore, follow, and understand legal values and a sense of justice that lives in the community as well as taking into the good and bad qualities of the defendant. The judge’s responsibility to find the law and determine the law on a case that is resolved in connection with that, the judge’s consideration, especially during the pandemic the judge is obligated to explore and see the condition of the defendant in commiting a criminal act. Are required to be able to make decision by looking at the motives or reasons of the perpetrator in commiting a crime so that judge based on his authority can use excuses and reson that relieve must also try to make decisions that are in line with the prevention of covid-19. This type of research is classified as juridical normative, namely research conducted by examining secondary legal materials or research based on documented standard rules which is also known as library research either through reading books of laws and regulations, materials and websites on the internet, interviews and other reference sources related to this thesis material. From the results of the research, there are three main things that can be concluded. First is the judge’s consideration in every decision during the pandemic. The second is the judge’s consideration in the form of forgiving reasons and mitigating reasons due to several factors such s the backbone of the family, confessing his actions, daring not to repeat It again and thirdly, there is the judge’s consideration of every decision issued by the judge’s, both within the defendant and the outside and the defendant. It is also a consideration for the judge is that there is no transmission either in court or in prison and to support policies issued by the government. Author suggestions, First, it is hope that judges as state officials who carry out the judiciary must really know the right of the defendant as regulated in law, second, judges in giving decisions must uphold a sense of justice in the midst of society, third, to the government and the law enforces to pay attention to their rights. Community rights and fixing solutions and legal problems faced by the parties as well as maintaining social order and public order. Keywords: Judge’s Consideration, Forgiving Reasons, Mitigating Reasons